2012
DOI: 10.3923/pjbs.2012.1126.1132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Date and Spacing on Growth and Yield of Fennel (Foeniculum vulgare Mill.) Under Irrigated Conditions

Abstract: Fennel (Foeniculum vulgare Mill.) plant is a medicinal aromatic herb and belongs to Apiaceae family. It has a rich nutritional value and has many medicinal usages. Very limited information is available in the literature about fennel cultivation and production practices. Therefore, this study was carried out to evaluate the effect of planting date and plant spacing and their interactive effects on yield, yield components and growth of Fennel under irrigation. Three planting dates (Oct. 1st, Nov. 1st and Dec. 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…This might be due to the fact that last week of November possibly received favorable condition for the quickest growth than those of other sowing time. This result agrees with the result obtained by [14] they reported that the sowing of fennel in the first date (20 th November) resulted in increase of all studied vegetative [15]. The plant height was observed significantly influenced by different nutrient application (Fig.…”
Section: Plant Height (Cm)supporting
confidence: 92%
“…This might be due to the fact that last week of November possibly received favorable condition for the quickest growth than those of other sowing time. This result agrees with the result obtained by [14] they reported that the sowing of fennel in the first date (20 th November) resulted in increase of all studied vegetative [15]. The plant height was observed significantly influenced by different nutrient application (Fig.…”
Section: Plant Height (Cm)supporting
confidence: 92%
“…Whereas the low yield at the late sowing date was caused by the plant quickly entering the reproductive stage, which left inadequate time for vegetative growth (Sharangi, 2014, Rahnavard et al, 2010 In addition to, early seeding of black cumin plants revealed an increase in plant height and an increase in the number of main and secondary branches each plant (Al-Zubaidy et al, 2020) additionally, the early cultivation of fennel resulted in a considerable increase in plant height, beside an increase in the number of branches and fruits each plant (Al-Dalain et al, 2012).…”
Section: Data In Tablementioning
confidence: 99%
“…According to the World Health Organization, medical plants are responsible for the health of more than 80% of the world's population in developing nations, while the usage of chemical compounds derived from medicinal plants is expanding in industrialized countries (Canter et al, 2005). Fennel is a herbal, perennial, fragrant plant with hermaphrodite owers and open pollination that is native to the Mediterranean region (Al-Dalam et al, 2012). The seed of the fennel plant is the commercial portion, which is used either directly or to extract essential oils.…”
Section: Introductionmentioning
confidence: 99%